2011
DOI: 10.1089/cap.2011.0011
|View full text |Cite
|
Sign up to set email alerts
|

Informant Discrepancies in Clinical Reports of Youths and Interviewers' Impressions of the Reliability of Informants

Abstract: Objective: In this study the authors examined whether discrepancies between parent and youth reports of the youth's emotional and behavioral functioning are related to interviewers' reliability ratings of parents and youths. Methods: In a consecutive case series analysis of 328 parents and youths aged 11-17 years, parents and youths provided reports of youth emotional and behavioral functioning and participated in structured clinical interviews. At the conclusion of the interviews, interviewers rated the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In another study on victimization and bullying among 73 children among 46 classrooms and 18 schools (Bonnet, Goossens, & Schuengel, 2011), the authors reasoned that as the average number of children in a classroom was 1.6, the design effect must be smaller than 2, and they chose the single-level regression analysis rather than the multilevel model. From our literature review in PsycINFO and ERIC, we found many similar studies in the field of education using this rule as a justification for not using multilevel models for multilevel/clustered data (e.g., Bouman et al, 2012;De Los Reyes et al, 2011;Deng et al, 2006;Hong & You, 2012;Linnenbrink-Garcia, Rogat, & Koskey, 2011;Ly, Zhou, Chu, & Chen, 2012;Von GrĂŒnigen, Kochenderfer-Ladd, Perren, & Alsaker, 2012;Wong et al, 2006). This rule was also commonly used in other research areas such as psychology (e.g., Corte & Zucker, 2008;Wagner, Christ, Pettigrew, Stellmacher, & Wolf, 2006), business (Qureshi & Fang, 2011), and medical science (Fuentes, Hart-Johnson, & Green, 2007).…”
mentioning
confidence: 89%
“…In another study on victimization and bullying among 73 children among 46 classrooms and 18 schools (Bonnet, Goossens, & Schuengel, 2011), the authors reasoned that as the average number of children in a classroom was 1.6, the design effect must be smaller than 2, and they chose the single-level regression analysis rather than the multilevel model. From our literature review in PsycINFO and ERIC, we found many similar studies in the field of education using this rule as a justification for not using multilevel models for multilevel/clustered data (e.g., Bouman et al, 2012;De Los Reyes et al, 2011;Deng et al, 2006;Hong & You, 2012;Linnenbrink-Garcia, Rogat, & Koskey, 2011;Ly, Zhou, Chu, & Chen, 2012;Von GrĂŒnigen, Kochenderfer-Ladd, Perren, & Alsaker, 2012;Wong et al, 2006). This rule was also commonly used in other research areas such as psychology (e.g., Corte & Zucker, 2008;Wagner, Christ, Pettigrew, Stellmacher, & Wolf, 2006), business (Qureshi & Fang, 2011), and medical science (Fuentes, Hart-Johnson, & Green, 2007).…”
mentioning
confidence: 89%
“…60 Regarding the discrepancy between parent and child reports of anxiety, it is noteworthy that cross-informant disagreements are a norm rather than the exception in assessment of child psychopathology. 61,62 It is possible that children do not perceive their anxiety symptoms as being as troublesome as their parents do, which would attenuate the change in child self-report from pretreatment to posttreatment. Thus, parent ratings commonly reveal greater levels of anxiety in children with ASD than child selfreports.…”
Section: Figurementioning
confidence: 99%
“…Thus, one cannot simply take reports from an adolescent's caregivers, compute their scores, and then choose a single caregiver's report at random to use in research or clinical work, assuming that conclusions drawn from one report will mirror those from the other. Consequently, researchers and practitioners alike often encounter a great deal of uncertainty making decisions when multiple informants' reports yield distinct conclusions (e.g., De Los Reyes et al 2011d;Hawley and Weisz 2003;Yeh and Weisz 2001).…”
Section: Introductionmentioning
confidence: 99%